Interpreting the Peace - Kelly, M. author. aut Link
XI, 237 p.
Keywords: Analysing the issues of language that faced international forces carrying out peace operations in Bosnia-Herzegovina in the 1990s, this book examines how differences of language were an integral part of the conflicts in the country and in what way the multinational UN and NATO forces faced their own problems of communication and language support.